2011
DOI: 10.4314/ijbcs.v5i2.72097
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS knowledge, sexual behaviour and condom use among commercial motorcyclists in Lagos State, Nigeria

Abstract: The incidence of HIV/AIDS infection within our society has gotten to an alarming proportion especially as it affects our youths, the group to which majority of our commercial motorcyclists belong. This prompted the need to assess the level of awareness, knowledge and preventive measures by these stakeholders towards HIV/AIDS in the face of cultural beliefs, habits and ignorance. A total number of 345 questionnaires containing well-structured questions relating to the subject matter were administered to commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…A similar age bracket was observed among motorcycle riders in Lagos and Benin Cities, Southern, Nigeria and Thailand. [11][12][13] Knowledge are the first stage in the behaviour change continuum. In the case of HIV, it is almost certain that knowledge about a disease can lead individual adopting required behaviour, to protect against being infected, agreeing to being tested and consequently lead to a significant reduction in stigma and discrimination against those infected with HIV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar age bracket was observed among motorcycle riders in Lagos and Benin Cities, Southern, Nigeria and Thailand. [11][12][13] Knowledge are the first stage in the behaviour change continuum. In the case of HIV, it is almost certain that knowledge about a disease can lead individual adopting required behaviour, to protect against being infected, agreeing to being tested and consequently lead to a significant reduction in stigma and discrimination against those infected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that majority of commercial motorcyclists were aware and believed in the existence of HIV/ADS, similar to that observed in Benin and Lagos cities in Nigeria where over 95% of the respondents had heard about the disease called AIDS. [12,13] The general high levels of HIV/AIDS awareness in Nigeria might be due to increased mass media campaigns going on globally and within the country on the infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents with no previous history with rabies were more likely to adopt uncorrect health practices. This result could be explained by the lack of regular rabies interventions in the study areas, involving and educating communities, as reported by Ojieabu et al (2011). Indeed, Burkina Faso has never developed a rabies control program (Dodet et al, 2010).…”
Section: Discussionmentioning
confidence: 91%